Tunisian Women's Activism Two Years After the Revolution: Looking Beyond Divisions and Challenges - Daniele, G. (BRISMES Conference, 2013)
Taking firstly into consideration the contemporary debate on the proliferation of transnational examples of political activism between women across the Maghreb and those from the Northern side of the Mediterranean, my analysis evaluates the potential impacts of such cross-border networking in relation to the tough topic of international aid policy. Using both theoretical analysis and evaluation of the results of my fieldwork, I focus on the political strategies and practices suggested by a number of women’s organisations in the direction of promoting a new language regarding women’s rights along with sharing transnational public spheres. Within the ‘post-revolution’ frame, the research tries to critically combine the analysis on women’s claims and struggles with the most institutionalised programs of international aid about gendered issues in order to respond to the events sparked by such uprisings. In pursuing this line of research, I concentrate my attention on the case of Tunisia, since, due to the promulgation of the Personal Status Code in 1956, it has represented both one of the first models for women’s emancipation in the MENA region, and the country where it all began. Whilst the current debate on internal contradictions between Islamist and secular women’s approaches has grown, my paper examines the transnational discourse dealing with women’s and feminist networks from one side of the Mediterranean to the other, and the ways through which they have been influenced and transformed by the increasing power of international aid assistance.